Effects of Debt Policy in Islamic Perspectives and Capital Structure Implications on Profitability Telecommunication Services Companies in Indonesia - Suhayati, Ely; H. Alhilo, Mahmad Hasan (IKONOMIKA, 2021)
Debt used in capital excessive composition for Telecommunication Company's business development has decreased profitability company's. In Islamic perspective, debt concept is represented in a loan form, with not additional elements that will lead to ribawi practice. This study purpose is to determine effect of debt policy in an Islamic perspective and capital structure that has implications on profitability telecommunications service companies in Indonesia. The method used is descriptive and verification methods with a quantitative approach, the sample used in this research is 4 telecommunication service companies listed on Indonesia Stock Exchange and last 5 years annual financial reports, so that data amount in this study is 20 data and analysis tools used are Multiple Linear Regression, Correlation Coefficient, Coefficient of Determination, and T-Test. This study results indicate that Debt Policy in Islamic Perspective has a moderate effect and has a positive correlation on profitability, while capital structure has a moderate effect and has a negative correlation on profitability telecommunication service companies in Indonesia.